Muhadaroh as Pesantren-Based Oral Da'wah Communication: Developing Students' Public Speaking, Religious Language, and Digital Media Readiness - Sakira Maulana Amin; Jamilah (WISE Pendidikan Indonesia, 2026)
This study examines muhadaroh as pesantren-based oral da'wah communication training for developing students' public speaking, religious language use, and digital media readiness. Although practiced in a face-to-face setting, muhadaroh is relevant to the intersection of language, communication, and digital da'wah because students must construct Islamic messages ethically and contextually for physical and mediated audiences. This qualitative descriptive study with a phenomenological orientation was conducted at Mafatihul Huda Islamic Boarding School, West Tanjung Jabung Barat. Data were gathered through observation, semi-structured interviews with the pesantren head, instructor, and participating students, and documentation, then analyzed through reduction, thematic display, conclusion drawing, and triangulation. Findings show that muhadaroh is implemented through MC practice, Qur'anic recitation, sholawat, berzanji or nadzom, speech delivery, evaluation, and closing prayer. The activity strengthens speech organization, vocal delivery, confidence, audience awareness, Islamic message construction, and communicative identity. Its implementation is supported by mentoring, regulation, and a conducive environment, but constrained by low interest, limited audio facilities, anxiety, and timing. The study contributes a contextual model for linking pesantren oral communication pedagogy with future digital da'wah literacy.